Engineered Flock House Virus for Targeted Gene Suppression Through RNAi in Fruit Flies (Drosophila melanogaster) in Vitro and in Vivo - Taning, Clauvis N. T.; Christiaens, Olivier; Li, XiuXia; Swevers, Luc; Casteels, Hans; Maes, Martine; Smagghe, Guy (Frontiers in Physiology, 2018)
RNA interference (RNAi) is a powerful tool to study functional genomics in insects and the potential of using RNAi to suppress crop pests has made outstanding progress. However, the delivery of dsRNA is a challenging step in the development of RNAi bioassays. In this study, we investigated the ability of engineered Flock House Virus (FHV) to induce targeted gene suppression through RNAi under in vitro and in vivo condition. As proxy for fruit flies of agricultural importance, we worked with S2 cells as derived from Drosophila melanogaster embryos, and with adult stages of D. melanogaster. We found that the expression level for all of the targeted genes were reduced by more than 70% in both the in vitro and in vivo bioassays. Furthermore, the cell viability and median survival time bioassays demonstrated that the recombinant FHV expressing target gene sequences caused a significantly higher mortality (60-73% and 100%) than the wild type virus (24% and 71%), in both S2 cells and adult insects, respectively. This is the first report showing that a single stranded RNA insect virus such as FHV, can be engineered as an effective in vitro and in vivo RNAi delivery system. Since FHV infects many insect species, the described method could be exploited to improve the efficiency of dsRNA delivery for RNAi-related studies in both FHV susceptible insect cell lines and live insects that are recalcitrant to the uptake of naked dsRNA.